Conservative Management of Pancreatic Pseudocysts in Children with Acute Lymphoblastic Leukemia - Spraker, Holly L. (2009)
Treatment with asparaginase for acute lymphoblastic leukemia (ALL) can cause acute pancreatitis. Complication of pancreatitis by pancreatic pseudocyst formation can prolong the hospital stay, delay chemotherapy, and necessitate long-term parenteral nutrition. We report five children with ALL who developed acute pancreatitis complicated by pancreatic pseudocysts. They required modifications to their chemotherapy regimen and prolonged parenteral nutrition but no surgical intervention. All five patients survive in first remission and their pseudocysts resolved after 3 to 37 months or continued to decrease in size at last follow-up. These cases illustrate that non-surgical management of pancreatic pseudocyst is safe, though pseudocyst resolution may require many months. In addition, these patients demonstrate that oral feeding can be initiated after the acute episode of pancreatitis resolves even if a pseudocyst is present.